A new approach to keeping your best on board : you know what entices your most talented employees to leave, but do you know what encourages them to stay? - Johnson, Lauren Keller (2007)
Looks at steps an organisation can take to encourage employees to stay, as well as ways in which individual managers can support the organization's efforts.